Yield combining ability and components in two groups of inbred lines of maize. - Guerrero-Guerrero, César (2011)
The objective of thiswork was to estimate the effects of the General CombiningAbility (GCA) of inbreed lines, and Specifi c CombiningAbility (SCA) of its crosses, and to evaluate its usein maize hybridization program. The present work wasconducted in two stages; in year 2006 the crosses were doneat the experimental station from Universidad AutónomaAgraria Antonio Narro Unidad Laguna (UAAANUL), andevaluation of the crosses was conducted in year 2007,at two localities and in three environments: UAAAN’sexperimental station during spring and summer cycles,Niagara and Aguascalientes Municipality during the springcycle. The genetic material used were two groups of inbredlines, the fi rst formed by four inbred lines from UAAANUL,and the second group was formed by ten inbred lines fromCentro Internacional para el Mejoramiento del Maíz yTrigo (CIMMYT). The estimation of General CombiningAbility (GCA) and Specifi c Combining Ability (SCA) wereobtained using a test of line x line. CML254 (10.88 t/ha)and AN447 (6.64 t/ha) had the highest effects of GCA forboth groups. The highest effects of SCA were for CML264x AN447 (128.8 t/ha) and CML247 x AN123 (116.2 t ha-1). These results show that is possible to structure a maizehybridization program, using the best inbred lines fromCIMMYT and UAAANUL.